Development of E-module of Fluid Physics Based on Problem-Based Learning (PBL) to Improve Motivation and Learning Outcomes of Grade XI Students of SMAN 4 Bagan Sinembah - Hafni, Fauziah; Fakhruddin , Fakhruddin; Yennita , Yennita (FKIP - Universitas Riau, 2025)
Technological advances have an impact on the use of learning media used in schools. This causes educators to develop teaching media that are appropriate to students' needs. One of the teaching media that can be designed according to students' abilities is e-modules. Initial findings indicate that the dominance of the use of less attractive printed books reduces students' motivation and learning outcomes. The purpose of this study was to develop a fluid physics e-module based on Problem-Based Learning (PBL) to improve motivation and cognitive learning outcomes of grade XI high school students. The method used was Research and Development (R&D) with the ADDIE model. Research data came from needs analysis, expert validation, teacher and student response questionnaires. The implementation stage of this PBL data used Nonequivalent Control Group Design and the data viewed were motivation data and cognitive learning outcomes. The results showed that the e-module developed obtained valid criteria by expert validators, and practicality by teachers and students obtained a very good category. The experimental class using the e-module showed higher motivation and cognitive learning outcomes than the control class. Data were analyzed using MANOVA which showed an increase in learning motivation by 52.9% and cognitive outcomes by 30.1%. The PBL e-module has proven to be effective and feasible to implement to improve physics learning.